Q: 2x - 3 equals 4x plus 9?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

2x - 4x + 3 = 0 -2x + 3 = 0 2x = 3 x = 3/2 = 1.5

2x + 2 = 4x -1 2x = 3 x = 1.5

6x + 3 = 2x + 5 4x = 2 x=1/2

4x + 2 = 2x + 5 Subtract through by 2x 2x + 2 = 5 Subtract through by 2 2x = 3 Divide through by 2 x = 1.5 ■

8x + 5x + 2x + 4x = 114 19x = 114 x = 6 then 5x + 3 = 5*6 + 3 = 33

Related questions

2x = 4x + 3 -2x = 3 x = -3 / 2

2x+17 = 4x-3 2x-4x = -3-17 -2x = -20 Answer: x =10

4x + 2 + 2x - 2x = 14 4x = 14 - 2 4x = 12 x = 3

4x + 3 = -3 + 2x + 14 2x + 3 = -3 +14 2x + 3 = 11 2x = 8 x=4

2x - 4x + 3 = 0 -2x + 3 = 0 2x = 3 x = 3/2 = 1.5

x=3

2x + 2 = 4x -1 2x = 3 x = 1.5

6X + 3 = 2X + 19Subtract 3 from each side:6X = 2X +16Subtract 2X:4X = 16Divide by 4X = 4

Simplify 4x + 3 = 2x + 8 2x = 5 x =2½

7

4x+9=2x-6 2x=-15 x=-7.5 x equals -7.5.

2x = x2 + 4x - 3 x2 + 2x - 3 = 0 (x - 1)(x - 2) = 0